Literature Review: Efektivitas Edukasi Kreatif dan Inovatif dalam Meningkatkan Pengetahuan Gizi Seimbang pada Anak Sekolah Dasar (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Knowledge of balanced nutrition among elementary school children remains low, despite its importance in developing healthy eating habits from an early age. This study aims to analyze the effectiveness of creative and innovative educational media in improving knowledge of balanced nutrition among elementary school children. The method used was a literature review by examining articles obtained from the Google Scholar and SINTA databases. The articles analyzed met the inclusion criteria, namely being published between 2020 and 2025, available in full text format, involving elementary school children as respondents, and measuring changes in nutritional knowledge after educational interventions. Data analysis techniques were carried out using descriptive qualitative techniques by grouping research findings based on the type of educational media, the form of intervention, and the results of increased nutritional knowledge, then comparing the research results to identify patterns of media effectiveness. The results of the review of five articles showed that the use of educational media such as animated videos, educational games, comics, posters, and the combination method Nutriedutainment proved effective in improving knowledge of balanced nutrition among elementary school children. Media that involve active student participation and the use of more than one sense tend to provide more optimal knowledge gains compared to conventional media, so they can be recommended as supporting strategies in implementing nutrition education in elementary schools